Readiness of graduate school educational support staff for digital-based distance education - Saiful Bakhri; Siswantoyo Siswantoyo; Eny Kuswandari; Syahri Ramadan; Siti Amironah; Siwi Widiastuti; Ririn Susetyaningsih; Andhita Mustikaningtyas (Jurnal Pendidikan Vokasi, 2025)
Digital transformation and the implementation of distance education require the readiness of educational support staff as key enablers of technology-based academic services, particularly in the context of vocational and applied higher education. This study aims to analyze the readiness of educational support staff in supporting digital-based distance education in terms of digital literacy, understanding of distance education policies, and the capacity to manage online learning systems. The study employed a descriptive sequential explanatory mixed-methods design. Quantitative data were collected through a Likert-scale questionnaire administered to educational support staff, while qualitative data were obtained through semi-structured interviews. The results indicate that 65% of educational support staff demonstrated moderate to good levels of digital literacy, 60% showed a moderate level of understanding of distance education policies, and only approximately 55% exhibited optimal readiness in managing online learning systems. Qualitative findings reveal that limited access to continuous professional training, diverse educational backgrounds, and uneven institutional support constitute the main barriers to staff readiness. This study concludes that the readiness of educational support staff needs to be systematically strengthened to ensure the effectiveness and sustainability of digital academic services and distance education.  The contribution of this study lies in providing empirical evidence to support capacity-building strategies and institutional policies aimed at strengthening human resource readiness for digital transformation in vocational and applied higher education.